DIGITALISASI PENDIDIKAN MELALUI PELATIHAN MICROSOFT WORD BAGI PESERTA DIDIK SMPN 1 TROWULAN - Lintang Ramadhani; Devri Bayu Perdana Putra; Mochammad Alhafis Havian; Siti Nur Mazro’atin Nisa; Alvin Barka Andiya (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service program focused on improving the digital literacy of students at SMPN 1 Trowulan through Microsoft Word training. The main problem faced was students' low skill level in using word processing applications due to limited facilities, limited computer practice, and the predominant use of smartphones over computers. The activity method consisted of initial observation, development of training modules, implementation of step-by-step practice, intensive mentoring, and evaluation of results. The training materials included an introduction to basic features, document organization, insertion of images and tables, and preparation of reports in accordance with academic standards. The results showed a significant improvement in students' digital skills, demonstrated by their ability to create simple documents, adjust text formatting, and compile neat reports. Furthermore, the training fostered learning motivation, increased self-confidence, and encouraged students' creativity in utilizing technology. The program's impact was felt not only by students but also by teachers and the school through the availability of training modules that can be used continuously. Thus, this Microsoft Word training is an important first step in realizing the digitalization of education at SMPN 1 Trowulan.